On the Centenary of the Birth of Luis Sánchez Belda (1920-1984) - de la Cruz Herranz, Luis Miguel (Revista General de Información y Documentación, 2021)
Luis Sánchez Belda has been one of the most important and influential archivists in the profession in recent times. Arriving very soon at the National Historical Archive, in 1946, he developed an important and continuous work in this center until his death in 1984, whose address he held since 1955. The years 1968-1977 supposed a parenthesis when he was appointed Director General of Archives and Libraries, among whose main achievements we must highlight the creation of the General Archive of the Administration in Alcalá de Henares (1969). His contributions to archival science were remarkable, drawing attention to the developments that were taking place outside our borders, especially in the fields of preservation and restoration of documents, archive buildings, microfilm and archival bibliography.
Keywords: Luis Sánchez Belda; National Historical Archive; General Directorate of Archives and Libraries; Archival Science; Preservation and restoration of documents; Archive buildings; Microfilm; Archival bibliography